Question regarding rural land ownership rights in Ethiopia - Kassa Belay (한국농촌경제연구원, 2004)
This study reveals that the land tenure system was the main obstacle to general rural development in the pre-land reform Ethiopia. Although the 1975 land reform freed the peasantry from merciless exploitation by the landlord class, through a series of misguided polices, the military regime placed the peasants before an impassable barrier. The study shows also that the current government maintains the state ownership of land and pursues policies concerning the allocation, transfer and redistribution of land that are closely akin to those of the military regime. Furthermore, the results of study point to the fact that state ownership of land and the latent fear of future redistribution have created a sense of uncertainty, which in turn is translated in reluctance to invest in long-term land improvement measures.
Keywords: land fragmentation; land redistribution; ownership rights; state ownership; tenure insecurity; usufruct rights.; land fragmentation; land redistribution; ownership rights; state ownership; tenure insecurity; usufruct rights.